Clostridioides difficile infection in solid organ and hematopoietic stem cell transplant recipients: A prospective multinational study. Issue 1 (13th December 2021) - Blumberg, Emily A.; Collins, Gary; Young, Jo‐Anne H.; Nguyen, M. Hong; Michonneau, David; Temesgen, Zelelem; Origȕen, Julia; Barcan, Laura; Obeid, Karam M.; Belloso, Waldo H.; Gras, Julien; Corbelli, Giulio Maria; et al.
Abstract: Background: Clostridioides difficile infection (CDI) is a significant cause of morbidity and mortality in recipients of solid organ transplant (SOT) or hematopoietic stem cell transplant (HSCT). In retrospective single center analyses, severe disease and relapse are common. We undertook an international, prospective cohort study to estimate the response to physician determined antibiotic treatment for CDI in patients with SOT and HSCT. Methods: Adults with a first episode of CDI within the first 2 years of SOT or HSCT were enrolled. Demographics, comorbidities, and medication history were collected, and over 90 days of follow‐up clinical cure, recurrences, and complications were assessed. Logistic regression was used to study associations of baseline predictors of clinical cure and recurrence. Odds ratios (ORs) and 95% confidence intervals (CIs) are cited. Results: A total of 132 patients, 81 SOT and 51 HSCT (32 allogeneic), were enrolled with a median age of 56 years; 82 (62%) were males and 128 (97%) were hospitalized at enrollment. One hundred and six (80.3%) were diagnosed by DNA assay. CDI occurred at a median of 20 days post‐transplant (interquartile range, IQR: 6–133). One hundred and eight patients (81.8%) were on proton pump inhibitors; 126 patients (95.5%) received antibiotics within the 6 weeks before CDI. The most common initial CDI treatments prescribed, on or shortly before enrollment, were oral vancomycin alone (50%) and metronidazole alone (36%). Eighty‐three percent (95% CI: 76, 89) of patients had clinical cure; 18% (95% CI: 12, 27) of patients had recurrent CDI; global clinical cure occurred in 65.2%. Of the 11 patients who died, two (1.5% of total) were related to CDI. In multivariable logistic regression analyses, the type of initial treatment was associated with clinical cure ( p = .009) and recurrence ( p = .014). A history of cytomegalovirus (CMV) after transplant was associated with increased risk of recurrence (44% with versus 13% without CMV history; OR: 5.7, 95% CI: 1.5, 21.3; p = .01). Conclusions: Among adults who develop CDI after SOT or HSCT, despite their immunosuppressed state, the percentage with clinical cure was high and the percentage with recurrence was low. Clinical cure and recurrence varied by type of initial treatment, and CMV viremia/disease was associated with an increased risk of recurrence.